Elementary Surveying : An Introduction to Geomatics - Ghilani, Charles D. (Pearson, 2022)
"This 16th Edition of Elementary Surveying: An Introduction to Geomatics is a readable text that presents basic concepts and practical material in each of the areas fundamental to modern surveying (geomatics) practice. It is written primarily for students beginning their study of surveying (geomatics) at the college level. Although the book is introductry to the practice of surveying, its depth and breadth also make it ideal for self-study and preparation for licensing examinations. This edition includes more than 400 figures and illustrations to help clarify discussions, and numerous example problems are worked to illustrate computational procedures. Throughout the book, the reader will find quick response (QR) codes. Some of the videos present instruction on solving specific problems in the book or demonstrate field procedures when using surveying instruments. Others, such as in Chapters 3, 4, 6, 9, 13, - 18 present enhanced instruction on the material in the book presented by the author and Dr. Thomas Seybert. The "What's New" section below show list the chapters where this enhanced instruction is available. The QR codes indicate that a video lesson on material presented in the book is available from the companion website for this book at http://www.pearsonhighered.com/ghilani"